The Impact of Blood Pressure and Visceral Adiposity on the Association of Serum Uric Acid With Albuminuria in Adults Without Full Metabolic Syndrome - Krajcoviechova, Alena; Tremblay, Johanne; Wohlfahrt, Peter; Bruthans, Jan; Tahir, Muhmmad Ramzan; Hamet, Pavel; Cifkova, Renata (American journal of hypertension, 2016)
BACKGROUND: The impact of metabolic phenotypes on the association of uricemia with urinary albumin/creatinine ratio (uACR) remains unresolved. We evaluated the association between serum uric acid and uACR in persons with 0, and 1-2 metabolic syndrome (MetS) components and determined the modification effects of visceral adiposity index (VAI), mean arterial pressure (MAP), and fasting glucose on this association. METHODS: Using data from a cross-sectional survey of a representative Czech population aged 25-64 years (n = 3612), we analyzed 1,832 persons without decreased glomerular filtration rate <60ml/min/1.73 m2, diabetes, and MetS. MetS components were defined using the joint statement of the leading societies. RESULTS: Of the 1,832 selected participants, 64.1% (n = 1174) presented with 1-2 MetS components (age 46.3±11.2; men 51.7%), whereas 35.9% (n = 658) were free of any component (age 39.4±10.0; men 34.2 %). In fully adjusted multiple linear regression models for uricemia, uACR was an independent factor for increase in uric acid levels only in persons with 1-2 MetS components (standardized beta (Sβ) 0.048; P = 0.024); however, not in those without any component (Sβ 0.030; P = 0.264). Uric acid levels increased by the interaction of uACR with VAI (Sβ 0.06; P = 0.012), and of uACR with MAP (Sβ 0.05; P = 0.009). Finally, the association of uACR with uricemia was confined to persons whose VAI together with MAP were ≥the median of 1.35 and 98mm Hg, respectively (Sβ 0.190; P < 0.001). CONCLUSIONS: We demonstrated a strong modification effect of VAI and MAP on the association between uACR and uricemia, which suggests obesity-related hypertension as the underlying mechanism.
Keywords: metabolic syndrome; Czech Republic; krevní tlak; Humans; biologické markery; Creatinine; Metabolic Syndrome; Uric Acid; kyselina močová; Biomarkers; Glomerular Filtration Rate; lidé; adipozita; Phenotype; Chi-Square Distribution; lineární modely; mean arterial pressure; Intra-Abdominal Fat; hypertenze; Albuminuria; Linear Models; Obesity; albuminurie; Hypertension; ledviny; Female; hodnoty glomerulární filtrace; uric acid; lidé středního věku; fenotyp; rizikové faktory; Male; průřezové studie; Hyperuricemia; hypertension; kreatinin; Blood Pressure; blood pressure; nitrobřišní tuk; Adult; Risk Factors; prediktivní hodnota testů; dospělí; Predictive Value of Tests; visceral adiposity index.; rozdělení chí kvadrát; Česká republika; Cross-Sectional Studies; albumin/creatinine ratio; Adiposity; Middle Aged; ženské pohlaví; mužské pohlaví; hyperurikemie; obezita; metabolický syndrom; Kidney